Rationally designed molecular beacons for bioanalytical and biomedical applications. (21st May 2015) - Zheng, Jing; Yang, Ronghua; Shi, Muling; Wu, Cuichen; Fang, Xiaohong; Li, Yinhui; Li, Jishan; Tan, Weihong
<x xml:space="preserve">Abstract</x> This review surveys advances in bioanalytical and biomedical applications of rationally designed MBs.